Prevalence of depression and anxiety among institutionalized elderly in Campina Grande, Paraíba (Research, Society and Development, 2022)
Objective: To estimate the prevalence of depression and anxiety among a population of institutionalized elderly and to verify possible associated factors. Method: The evaluation of the elderly took place in three phases: screening of cognitive ability through the application of the Mini-Mental State Examination - MMSE; collection of socioeconomic data through the application of a questionnaire; determination of the prevalence of Depression and Anxiety through the application of the Geriatric Depression Scale - GDE and the Beck Anxiety Inventory - BAI. The data were tabulated in absolute and relative frequency tables, considering the mean and standard deviation values, and the chi-square test (χ2) was applied with a significance level of 5%. Results: There was a significant correlation between the presence of chronic diseases and the prevalence of Depression (P-value: 0.024) in the sample, underlining the influence exerted by intra-institutional living conditions on the mental health of institutionalized elderly. A relatively high prevalence of anxiety was found, as well as moderate levels of depression in the sample. Conclusion: The profound impact exerted by the different material and symbolic conditions of intra-institutional existence on the individual subjectivity of each elderly person residing in Homes for the Aged is evidenced.